Alumnus User Satisfaction of Fakultas Keguruan Dan Ilmu Pendidikan Universitas Sebelas Maret - Murwaningsih, Tri; Wahyuningsih, Daru (Proceeding of International Conference on Teacher Training and Education, 2016)
Educational management is the management of educational resources in accordance withmanagement functions to achieve educational goals effectively and efficiently. Educationalresource consists of men, money, materials, methods, machine, market, minute, and information.Management functions such as planning, organizing, actuating, and controlling are performedsequentially. Controlling function is to monitor and evaluate the results of actuating function incomparison with the goals to be achieved. One effort in the controlling of FKIP UNS is thealumnus user satisfaction survey. Information survey results are used for policy-makingconsiderations in the improvement and development of quality improvement of students so thatalumnus users obtain qualified labor. Informations are obtained from the 39 agencies both formaleducational institutions (primary schools, junior high schools, senior high schools, and vocationalschools) or non-formal educational institutions in 2012. The research instrument is a questionnaireto determine the ten alumnus abilities. From the questionnaires showed that alumnus FKIP UNSincluding in the category of very capable in leadership skills, science, the use of informationtechnology, active in school organization. Alumnus FKIP UNS including in the category ofcapable in communication skills, teamwork, motivation and self-development, integrity, andentrepreneurship. Alumnus FKIP UNS including in the category of less capable in mastery of theEnglish.